STRATEGI PEMBERDAYAAN RUMAH ZAKAT DALAM MENGENTASKAN KEMISKINAN MELALUI PROGRAM SENYUM MANDIRI DI DESA MEKARJAYA, KABUPATEN PANDEGLANG - Uga Halia Dinan; Muhtadi Muhtadi (Jurnal Kommunity Online, 2022)
Rumah Zakat is a non-government organization (NGO) engaged in the humanitarian field by managing zakat, infaq, alms, waqf, and other humanitarian funds with the aim that they can be managed properly and channeled appropriately and effectively as well as productively. Self smile program. is an empowerment program carried out by Rumah Zakat with a focus on empowering small and micro businesses for the lower middle class to reduce poverty levels. The success of the independent smile program in Mekar Jaya Village is influenced by the empowerment strategy carried out by the village facilitator with Rumah Zakat. The purpose of this study was to determine: (1) the empowerment strategy of Rumah Zakat in alleviating poverty (2) the results of the empowerment of Rumah Zakat in alleviating poverty. By using a qualitative research methodology, the results of this study indicate that the strategy used by Rumah Zakat in alleviating poverty is the strategy proposed by Ismawan (Priyono, 1996) in Mardikanto and Soebianto (2012:170), namely: Human resource development, Institutional development group, Community (private) capital fertilization, productive business development, productive business development. From the research results, there are several empowerment results, namely economic, education, health, spiritual. From the results of the study, four indicators of empowerment results, three indicators are declared to have maximum results, but one indicator, namely spirituality, is still not optimal.